A Physiological Analysis of Desiccation Stress in the Green Tide Species Ulva stenophylloides and Ulva uncialis in the South Pacific - Javiera Mutizabal-Aros; Andrés Meynard; Loretto Contreras-Porcia (Journal of Marine Science and Engineering)
Global green tide blooms of the Ulva genus have been increasing due to human activities, with mass accumulation in Algarrobo Bay, Chile, causing ecological and social issues. In this area, five Ulva species were previously identified, with Ulva stenophylloides dominating across seasons and intertidal zones; Ulva uncialis was the second most abundant, mainly in winter. In this study, we tested the hypothesis that U. stenophylloides is more tolerant to desiccation than U. uncialis, explaining its dominance in the upper intertidal zone. Based on in vitro cultures, we assessed the impact of desiccation stress on weight, blade length, cellular activity, and lipoperoxide levels. In U. uncialis, desiccation treatment caused a decrease in weight; conversely, in U. stenophylloides, both control and desiccation treatments caused a slight decrease in weight. No significant differences (p > 0.05) in blade length or lipoperoxide levels as a function of culture time were detected in the control and desiccation treatment groups for both species. Furthermore, desiccation had no negative effects on the cellular activity of either species. Although the observed weight changes suggest that U. uncialis is more desiccation-tolerant than U. stenophylloides under the experimental conditions, the cellular activity and lipoperoxidation indicate high desiccation tolerance in both species, which partly explains their intertidal dominance.